An enneagram approach to strategy - Issam Tlemsani; Mohamed Ashmel Mohamed Hashim; Robin Matthews; Vera Ndrecaj; Rachel Mason-Jones (Administrative Sciences, 2023)
This conceptual paper examines how Enneagram as a personality typing system could be adopted as a meta-model across multiple domains. The enneagram strategy is a structural typology that many organisations and individuals use to effectively understand their business profiles and interpersonal patterns, despite scholars showing concerns about its robustness and dynamism. This paper extends the argument as to how the mechanics of the Enneagram are intrinsically interrelated with (a) organisational systems and networks, (b) organisational grammar, (c) supply chains, and (d) creativity. It also emphasizes the importance/close association of the Enneagram tool with interdependence, business model, networks, statics, and system dynamics. The paper uses a combination of research methods (theoretical, exploratory, and descriptive) to evaluate the adaptability of the enneagram. The findings demonstrate that enneagram as a strategy could be applied to various business phenomena but requires more cross-domain empirical research. The enneagram can also be used to develop meta-models/toy models that can relate to the organisational outcomes by integrating tangible and intangible process assets. This paper reliably lays a set of principles/foundations to launch the enneagram approach to a complex, broad, systematic, and creative scope.
Keywords: 350; creativity; enneagram; grammar; meta-model; networks; organisation; systems